3D MODELING ANIMATED OBJECTS - Кучеров, Д. П.; Моргун, К. О. (Science-based technologies, 2015)
The article discusses current approaches of creation animated three-dimensional shapes. On the basis of analyzing the laws of real three-dimensional figures is created program model of three-dimensional objects with the ability to move. The modelling process is decomposed into five interrelated stages of development: the creation of a skeleton, its texturing, rigging, animation and rendering. Each step can be implemented in several ways. Considered that implementation the elements of the model can be manually and by software. Selected variants are compared by the number of operations and time-consuming. The article provides a detailed analysis of the labour intensity, defined steps that require the most time effort. The technique, which allows to determine the most suitable software for the task of creating three-dimensional objects in terms of time spent and possible approaches to reduce them in the performance of the tasks of this sort are determined.